Use of phytotherapy in treating diabetic foot in older adults: an integrative review - José Mateus Pires; Gabriella Farias Lopes; Caroline Ribeiro de Sousa; Francisco Gerlai Lima Oliveira; Rodrigo Lopes de Paula Souza; Janaína Fonseca Victor Coutinho; Marília Braga Marques (Universidade Federal do Ceará, 2023)
Objective: to identify the scientific evidence on herbal medicines used in treating diabetic foot in older adults. Methods: an integrative review conducted in the Medical Literature Analysis and Retrieval System, SCOPUS, EMBASE, Web of Science and Latin American and Caribbean Health Sciences Literature databases. The Rayyan platform was used as a supporting tool for archiving, organizing and selecting articles. Results: the search resulted in 158 articles. After identifying, selecting, evaluating eligibility, systematization and performing a full reading of the articles, the final sample consisted of 10 articles. We identified herbal medicines derived from Calendula officinalis, Ageratina pichinchensis, Phellodendron chinense, Curcumin phytosome, Capsicum spp., Rehmannia Glutinosa and Astragalus membranaceus. Conclusion: investigations of herbal compounds derived from four plants used in treating diabetic foot in older adults predominated. Considerations for practice: supported by legislation, nurses can guide users interested in using phytotherapy as an accessible solution with proven efficacy.